CULTURAL TOURISM POTENTIAL IN CINTA ISLAND TELUK JERING TELUK KENIDAI VILLAGE KAMPAR REGENCY - Gressela "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research using  descriptive qualitatatife research method, there is a purpose  to find out what potential does the Cinta Island Tourism Object have, the development of the object Cinta Island Tourism, as well as what problems are faced in developing Tourism Objects on Cinta Island, Teluk Jering Village, District Kampar. For this season, an analysis is needed in the development of an appropriate tourist attraction and can be applied to the Cinta Island tour to make it more developed. So it can be concluded that the Cinta Island Tourism Object if well developed turns out have potential as a naturaln tourism object. Well developed turns out to have potential as a natural tourism object which is very interesting to be developed and the participationof the goverment, the private sector and the community is needed in its development, so that increase the number of domestic and foreign and tourists and can promote tourism, especially in the Mine District Kampar Regency. Keyword:Tourism Potential, Tourism Development, Tourist Attraction.